The decision-point-dilemma: Yet another problem of responsibility in human-AI interaction - Laura Crompton (Journal of Responsible Technology, 2021)
AI as decision support supposedly helps human agents make ‘better’ decisions more efficiently. However, research shows that it can, sometimes greatly, influence the decisions of its human users. While there has been a fair amount of research on intended AI influence, there seem to be great gaps within both theoretical and practical studies concerning unintended AI influence. In this paper I aim to address some of these gaps, and hope to shed some light on the ethical and moral concerns that arise with unintended AI influence. I argue that unintended AI influence has important implications for the way we perceive and evaluate human-AI interaction. To make this point approachable from both the theoretical and practical side, and to avoid anthropocentrically-laden ambiguities, I introduce the notion of decision points. Based on this, the main argument of this paper will be presented in two consecutive steps: i) unintended AI influence doesn’t allow for an appropriate determination of decision points - this will be introduced as decision-point-dilemma, and ii) this has important implications for the ascription of responsibility.